Investigation of Laminar Separation Bubble on Flat Plate with Adverse Pressure Gradient: Time-Averaged Flow Field Analysis - Yonglei Qu; Dario Barsi; Daniele Simoni; Pietro Zunino; Yigang Luan (International Journal of Aerospace Engineering)
The performance of turbomachinery blade profiles, at low Reynolds numbers, is influenced by laminar separation bubbles (LSBs). Such a bubble is caused by a strong adverse pressure gradient (APG), and it makes the laminar boundary layer to separate from the curved profile surface, before it becomes turbulent. The paper consists on a joint experimental and numerical investigation on a flat plate with adverse pressure gradient. The experiment provides detailed results including distribution of wall pressure coefficient and boundary layer velocity and turbulence profiles for several values of typical influencing parameters on the behavior of the flow phenomena: Reynolds number, free stream turbulence intensity, and end-wall opening angle, which determines the adverse pressure gradient intensity. The numerical work consists on carrying out a systematic analysis, with Reynolds Average Navier-Stokes (RANS) simulations. The results of the numerical simulations are critically investigated and compared with the experimental ones in order to understand the effect of the main physical parameters on the LSB behavior. For RANS simulations, different turbulence and transition models are compared at first to identify the adaptability to the flow phenomena; then, the influence of the three aforementioned parameters on the LSB behavior is investigated under a typical aggressive adverse pressure gradient. Boundary layer integral parameters are discussed for the different cases in order to understand the flow phenomena in terms of flow time-mean properties.